2013
DOI: 10.1021/ja409271s
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture by a Rhenium(I) Complex with the Aid of Triethanolamine

Abstract: A rhenium(I) tricarbonyl diimine complex with a N,N-dimethylformamide ligand captures one CO2 molecule in the presence of triethanolamine (TEOA), giving fac-[Re(I)(bpy)(CO)3{R2N-CH2CH2O-COO}] (bpy = 2,2'-bipyridine, R = CH2CH2OH). This could be a predominant complex in various photocatalytic CO2 reduction reactions using [Re(I)(N^N)(CO)3X](n+) (N^N = diimine ligand; X = monodentate ligand; n = 0, 1) type complexes in the presence of TEOA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
274
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(287 citation statements)
references
References 25 publications
13
274
0
Order By: Relevance
“…60 It is unknown whether or not TEOA coordinates to the Mn center during this process; however, previous studies with Re bipyridine photocatalysts have shown that CO 2 can bind to the metal center with the aid of TEOA, forming an O-bound Re−OC(O)OCH 2 CH 2 NR 2 complex. 61 68 In the original report of the photocatalytic ability of Mn(bpy)(CO) 3 Br by Takeda et al in 2014, the authors report slightly lower TONs for formate by only the Ru 2+ photosensitizer (TON = 25 after 12 h). 45 Although the [Ru(dmb) 3 ] 2+ photosensitizer also serves as a catalyst for CO 2 reduction, it is clear that the Mn complex enhances CO 2 reduction to formate by at least a factor of ∼2 in the homogeneous system and a factor of ∼3 in the heterogeneous UiO-67-Mn(bpy)(CO) 3 Br system.…”
Section: ■ Results and Discuissonmentioning
confidence: 99%
“…60 It is unknown whether or not TEOA coordinates to the Mn center during this process; however, previous studies with Re bipyridine photocatalysts have shown that CO 2 can bind to the metal center with the aid of TEOA, forming an O-bound Re−OC(O)OCH 2 CH 2 NR 2 complex. 61 68 In the original report of the photocatalytic ability of Mn(bpy)(CO) 3 Br by Takeda et al in 2014, the authors report slightly lower TONs for formate by only the Ru 2+ photosensitizer (TON = 25 after 12 h). 45 Although the [Ru(dmb) 3 ] 2+ photosensitizer also serves as a catalyst for CO 2 reduction, it is clear that the Mn complex enhances CO 2 reduction to formate by at least a factor of ∼2 in the homogeneous system and a factor of ∼3 in the heterogeneous UiO-67-Mn(bpy)(CO) 3 Br system.…”
Section: ■ Results and Discuissonmentioning
confidence: 99%
“…Consequently, every study focusses on hydrogen evolution by means of a sacrificial electron donor (usually triethanolamine or trimethylamine) to provide an oxidative half reaction to close the catalytic cycle. It is vital to understand the role of these sacrificial electron donors 78 such that we can replace them by recyclable electron donors. 79,80 Then, by combining this system with a water oxidation catalyst, sustainable solar fuel generation can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…This may suggest the necessary involvement of TEOA as both a sacrificial electron and proton donor in the photocatalyzed reaction. [22] Under the same CO 2 photocatalytic conditions as that of the TiO 2 -rGO-Re(PyBn)(CO) 3 Cl composite, TiO 2 nanoparticles produced no measurable CO or CH 4 ; this differs from the TiO 2 -catalyzed photo-reduction of CO 2 to produce CH 4 using 2-propanol as a sacrificial donor. [23] The photo-stability of the catalyst composite was then evaluated.…”
mentioning
confidence: 94%